Does debt market integration amplify the international transmission of business cycles during financial crises?. (July 2021) - An, Jiyoun; Kim, Kyunghun; Pyun, Ju Hyun
Highlights: Business cycle co-movement during financial crises differs in the type of debt integration. Simultaneous equations model is used for country-pair data of 57 countries, 2001–2013. Short-term debt integration drives business cycle synchronization during crises. Long-term debt integration leads to business cycle divergence during crises. Abstract: The international transmission of real business cycles during financial crises differs dramatically depending on the type of debt market integration. Using a bilateral country-pair dataset of 57 countries covering the period 2001–2013, we find robust empirical evidence that short-term debt integration drove business cycle synchronization during the global financial crisis (GFC) and European sovereign debt crisis. However, we also find that long-term debt integration cushioned the international transmission of business cycles during the crises. Our findings distinguish two transmission channels of financial shocks: the balance sheet effect through the integrated short-term debt market and risk-sharing through long-term debt market integration.